PERANCANGAN HOME AUTOMATION DALAM MENGONTROL TIRAI, MENDETEKSI KEBAKARAN, DAN KEAMANAN PADA PINTU (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2023)
One of the technological developments that is beneficial to humans is to minimize and assist humanperformance in controlling the house. Sometimes in the use and control of the house efficiency is stillnot maximized. The use of Arduino Uno is very diverse, namely it can be used to develop interactiveobjects, take input from various switches or sensors, control or control curtains, detect fires, andsecurity at doors. At present, most of the household control systems still use human power, forexample to open and close curtains, being oblivious to fire hazards, this makes human work slow andcareless. Arduino Control in Organizations can help users control home conditions.
Keywords: Keywords: Arduino, Smarthome, Fingerprint Sensor, Fire Sensor, LDR Sensor